Air pollution, emerging chemical exposures, and systemic lupus erythematosus: a meta-epidemiology study - Xu, Yaling; Pan, Hejing; Chen, Wu; Wang, Yehang; Li, Xuanlin; Dai, Qiaoding; Huang, Lin (Frontiers in Immunology, 2025)
ObjectivesThis meta-analysis evaluated the direction and strength of associations between air pollution, emerging chemical pollutants, and systemic lupus erythematosus (SLE) incidence, clarifying distinct relationships by pollutant type.MethodBy utilizing medical subject headings and keywords from the PubMed and EMBASE databases, a thorough search was conducted for published observational studies linking air pollution and SLE from inception until August 2024. The Newcastle-Ottawa Scale (NOS) was utilized to evaluate the quality of the studies. Statistical analyses were performed using STATA software (version 14.0), with the assessment of publication bias conducted through funnel plots and Egger’s test.ResultThis meta-analysis encompassed 8 studies published between 2018 and 2024, involving a total of 1,390,348 individuals. We assessed exposure to standard air pollutants and emerging chemical pollutants, specifically including perfluoroalkyl and polyfluoroalkyl substances (PFASs, a type of persistent chemical widely used in nonstick cookware and waterproof products) and bisphenol compounds (BPs, a synthetic chemical primarily used in plastic products and resins). These eight studies identified significant positive associations between SLE incidence and exposure to PM2.5 [OR = 1.16, 95% CI (1.02-1.32), I2 = 62.4%, p=0.031], NO2 [OR = 1.24, 95% CI (1.11-1.38), I² = 0.0%, P = 0.603], and PFASs [OR = 2.47, 95% CI (1.54-2.57)], while O3 exhibited a negative association [OR = 0.83, 95% CI (0.70-0.98), I² = 19.3%, P = 0.290]. No significant links were found for PM10 [OR = 1.11, 95% CI (0.90–1.36), I² = 66.3%, P = 0.031], SO2 [OR = 0.99, 95% CI (0.66-1.48), I² = 79.0%, P = 0.001], and BPs [OR = 1.26, 95% CI (0.80-1.99)]. Sensitivity analyses supported robustness without evidence of publication bias.ConclusionThe results of this meta-analysis suggest that air pollutants PM2.5 and NO2 may be potential environmental risk factors for SLE, while the negative correlation with O3 requires further research to validate its potential mechanisms. It is worth noting that although a study on PFASs showed a strong association with SLE, this finding requires further evidence due to the limited number of relevant studies currently available. These findings imply that improving air quality and strengthening regulation of emerging pollutants may reduce the disease burden of SLE. Based on the current strength of evidence, public health policies should prioritize reducing population exposure levels to PM2.5 and NO2, which may help reduce the potential risk of SLE onset. Concurrently, larger-scale studies should be conducted to confirm the association between other environmental pollutants such as PFASs and SLE, providing more comprehensive scientific evidence for the development of targeted environmental health policies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO (CRD42024581931).